A Within-Subject Before-After Study of the Impact of Antidepressants on Hemoglobin A1c and Low-Density Lipoprotein Levels in Type 2 Diabetes - Rohde, Christopher; Thomsen, Reimar W; Østergaard, Søren D (Journal of clinical psychopharmacology, 2022)
Data on the effect of treatment with antidepressant drugs on metabolic control in diabetes are sparse. In this controlled within-subject before-after study, the impact of initiation and discontinuation of antidepressant treatment on hemoglobin A1c (HbA1c) and low-density lipoprotein (LDL) levels in type 2 diabetes was estimated. All individuals with newly developed type 2 diabetes (first HbA1c ≥ 6.5%) between 2000 and 2016 in Northern and Central Denmark were identified using register-based health care data. Among these, we identified individuals initiating and discontinuing antidepressant treatment. Using a within-subject before-after design, we examined HbA1c and LDL in the 16 months leading up to and the 16 months after antidepressant treatment initiation or discontinuation, respectively. For comparison, we ran similar time trend analyses in a reference population of age- and sex-matched type 2 diabetes individuals not receiving antidepressant treatment. Mean HbA1c decreased after initiation of antidepressant treatment (-0.16%; 95% confidence interval [CI], -0.18 to -0.13%). In the reference population, no material change in HbA1c over time (-0.03%; 95% CI, -0.04 to -0.01%) was seen. Mean LDL decreased not only in antidepressant initiators (-0.17 mmol/L; 95% CI, -0.19 to -0.15 mmol/L) but also in the reference population (-0.15 mmol/L; 95% CI, -0.16 to -0.13 mmol/L). Among antidepressant discontinuers, there was also a decrease in HbA1c (-0.32%; 95% CI, -0.37 to -0.28%), with no change in the reference population (-0.02%; 95% CI, -0.04 to 0.00%). Decreases in LDL were found both in antidepressant discontinuers (-0.09 mmol/L; 95% CI, -0.14 to -0.04 mmol/L) and in the reference population (-0.16 mmol/L0; 95% CI, -0.18 to -0.13 mmol/L). Antidepressant treatment in type 2 diabetes may have a beneficial effect on glycemic control, as the decrease in HbA1c after discontinuation of antidepressants likely reflects remission of depression. Conversely, antidepressant treatment does not seem to affect LDL levels.